Knowledge and Beliefs of Breast Cancer Among Elderly Puerto Rican Women: Validation Process of Scales - Suárez-Pérez, Erick; Sánchez-Ayéndez, Melba; Oliver-Vázquez, Marlen; Vélez-Almodóvar, Hemilce; Rosario-Rosado, Rosa; Nazario-Delgado, Cruz (Puerto Rico Health Sciences Journal, 2016)
see manuscript